Original paperPercutaneous reduction of mitral valve regurgitation using the MitraClip system – immediate and 90-day follow-up of 3 cases - Kübler, Piotr; Kustrzycka-Kratochwil, Dorota; Telichowski, Artur; Witkowski, Tomasz; Banasiak, Waldemar; Jankowska, Ewa A.; Ponikowski, Piotr; Reczuch, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Treatment of hemodynamically significant valvular heart diseases has been the domain of cardiac surgery for decades. However, a promising novel method is the MitraClip system, involving percutaneous connection of insufficient valve leaflets with special cobalt-chrome clips. Our study presents clinical characteristics, course of treatment with the MitraClip system, and immediate and 90-day clinical and echocardiographic follow-up of the first 3 patients treated in our institution. Subsequently, based on data from the literature and our own experience, the current position around the world, and the target group of patients who are most likely to benefit from treatment using the MitraClip system, are discussed.